A Newly Identified Int22h1/Int22h2‐Mediated Xq28 Duplication Syndrome Case Misdiagnosed as Cerebral Palsy - Bastos, Paulo André Dias; Barbosa, Raquel (Journal of Pediatric Neurology, 2022)
Cerebral palsy (CP) is a nonprogressive, early-onset neurodevelopmental disorder affecting ∼2 to 3/1,000 children worldwide. It is characterized by movement/postural disabilities accompanied by sensitive, perceptual, cognitive, communicational, behavioral, and musculoskeletal perturbations. Many CP patients are thought to have genetic etiologies overlapping those of other neurodevelopmental conditions. Herein, we reported a newly discovered case (the 36th case to date) of a female patient (misdiagnosed with CP until age 19) with the rare X-linked intellectual disability syndrome resulting from an int22h1/int22h2-mediated Xq28 duplication. A microarray analysis revealed a ∼0.4 Mb duplication within the 154.1 to 154.6 Mb subregion of Xq28 (hg19, CRCh37), confirming a diagnosis of the rare int22h1/int22h2-mediated Xq28 duplication intellectual disability syndrome. Atypical T2 hyperintensities were also observed. This case report builds upon the limited cohort of X-linked intellectual disability syndrome patients and reiterates the growing observations pertaining to the phenotypic overlap between genetic CP cases and other neurodevelopmental disorders.
Keywords: chromosomal anomaly; X-linked intellectual disability; chromosomal microarray analysis; cerebral palsy; gene dosage